Using composite yield mechanism to mitigate seismic damage to exposed steel column base connections. (1st April 2021) - Cui, Yao; Wang, Fengzhi; Yang, Cancan; Li, Hao; He, Yangzi
Highlights: Composite Yield exposed column base connections were tested until ultimate state. Composite yield mechanism is able to mitigate damage to exposed column base. Composite yield mechanism results in enhanced strength and energy dissipation. The contribution from the interior anchors and exterior plate could be adjusted. An evaluation method is proposed to predict yield and ultimate moment strength. Abstract: A novel exposed column base (ECB) connection, featuring composite yield mechanism (i.e., a combination of anchor rod and base plate yielding), has been recently proposed in Japan for optimum seismic performance. This paper focused on investigating the effects of using composite yield mechanism on damage mitigation for ECB connections. In doing so, four two-thirds scale specimens, with different base connection configurations, were tested under combined flexure and axial load. Their performances were assessed and compared in terms of damage evolution, moment-rotation relationship and energy dissipation. The experimental results showed that for ECB connection with composite yield mechanism, both anchor rod and base plate will actively contribute to the moment resistance and energy dissipation. This can successfully postpone the interior anchor rod yielding and fracture, compared to the ECB connection with anchor rod yield mechanism. Meanwhile, the strain demands on exterior plate can be also released compared to the ECB connection with base plate yield mechanism. The relative contributions from anchor rod and base plate of ECB connection with composite yield mechanism can be controlled by changing the exterior plate thickness. In addition, an analytical method was proposed to predict the yield and ultimate moment strength for the Composite Yield ECB connection based on the principle of virtual work. The difference between predicted and measured moment strength is within 15%, showing the validity of the proposed method for moment strength prediction.